(untitled) (Journal of Chemical Engineering, 2014)
The commercialization of titanium dioxide-based heterogeneous photocatalysis continues to suffer from various limitations, the major shortcoming being the costly and time consuming post-treatment separation of very fine titanium dioxide particles. In order to eliminate this major hindrance, immobilization of titanium dioxide particles on various substrates continues to be an active area of research. In this work, polystyrene-supported titanium dioxide photocatalyst was prepared using a facile method. The photocatalytic activity of the developed photocatalysts was investigated by photodegradation of aqueous solutions of methylene blue andmethyl orange dyes under UV light for 24 h under non-stirred conditions. The recovery and reuse of the prepared photocatalysts was also investigated. The maximum percentage degradation of methyl orange and methylene blue dyes by the developed photocatalysts was found to be around 60 % and 66 % respectively. The ease of separation after use in addition to a facile, low cost-based method of fabrication and appreciable photocatalytic activity of the developed photocatalyst makes it a promising candidate to be explored further for large scale applications. DOI: http://dx.doi.org/10.3329/jce.v28i1.18103 Journal of Chemical Engineering, Vol. 28, No. 1, December 2013: 9-13